KUALITAS PELAYANAN PUSKESMAS TERHADAP PENGGUNA PROGRAM BPJS KESEHATAN DI PUSKESMAS PAGURAWAN - Mardiansyah Mardiansyah (JURNAL KESMAS DAN GIZI (JKG), 2019)
Health care for the poor patients is a complex and so important problem, so that all humans are entitled to proper health services. The Puskesmas is the leading party in health services, therefore the existence of the Puskesmas is very important. The purpose of this study was to determine the quality of service at Pagurawan Health Center to BPJS patients. This research was qualitative descriptive in nature at Pagurawan Health Center, Medang Deras District, Batubara Regency. Data collection techniques are carried out through interviews and documentation. Analysis of the data used in this study is descriptive data analysis. In this case the Pagurawan Health Center has shown good service by providing services that meet the expectations and satisfaction of BPJS patients, for example: the clarity of health financing is in very good category, the environmental security of the hospital is in good category, fairness in obtaining services is in sufficient categories, clarity about tasks and the functions of health workers is in good categories, and the availability and clarity of information is in very good categories.